MATHEMATICAL MODELSHVYDKOSTI WIND AND ITS RATIONALE PROBABILISTIC NATURE - , Н. О. (Municipal economy of cities. Series: «Economy science», 2013)
The main value that uniquely describe a mathematical model of the static and pulsating components of the wind velocity is justified by their probabilistic nature. Analyzed experimental data rate turbulence intensity, longitudinal integral length scale of turbulence and the exponential decay factor.